Intelligent reversible bus lane in Gävle: udvidet resumé - Pedersen, Dennis Bjørn (Proceedings from the Annual Transport Conference at Aalborg University, 2020)
The Swedish City of Gävle was hardly able to cope in recent years with the numbers of visitors to events and sports matches in the city. A consortium including Technolution was commissioned to develop an intelligent reversible bus lane. This lane is now finished – and it involves Dutch technology, such as DVM-Exchange and MobiMaestro.